Preparation method of lanthanum modified sulfide solid electrolyte
Through the combination of lanthanum-modified polyethylene oxide with bis(trifluoromethylsulfonyl)imide scandium and Li6PS5Cl electrolyte, a composite sulfide solid electrolyte is formed, which solves the challenges of lithium-ion batteries in terms of safety, energy density and cycle life, significantly improves the chemical stability and mechanical strength of the electrolyte, and improves the overall performance of the battery.
Patent Information
- Application Number
- CN202411824286.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-25
AI Technical Summary
Existing lithium-ion batteries have challenges in terms of safety, energy density and cycle life, and the chemical stability and mechanical strength of solid electrolytes are insufficient, which affects the overall performance of the battery.
By introducing lanthanum-modified polyethylene oxide (PEO), it improves its chemical stability and mechanical strength, and combines with bis(trifluoromethylsulfonyl)imide scandium and Li6PS5Cl electrolyte to form a composite sulfide solid electrolyte. The method includes preparing Li6PS5Cl electrolyte by solid phase sintering and obtaining lanthanum modified PEO-LiTFSI composite electrolyte by stirring and drying.
Significantly improves the chemical stability and mechanical strength of the electrolyte, improves conductivity and overall safety of the battery, enhances the battery's ability to operate in extreme environments, and allows operation over a wider voltage range.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sulfide all-solid-state batteries, and specifically relates to a method for preparing a lanthanum-modified sulfide solid electrolyte. Background Art
[0002] Currently, lithium-ion batteries using liquid electrolytes are the main choice for consumer electronics and electric vehicles, but their development is limited by numerous challenges regarding safety, energy density, and cycle life. The use of all-solid-state lithium metal batteries offers a possible solution to these problems.
[0003] PEO polymer electrolyte is easy to form a film and has good flexibility. For example, patent CN117096430A discloses a solid electrolyte technology field, particularly a PEO-based solid electrolyte with high ionic conductivity and good high-voltage stability and its preparation method, as well as its application in solid-state batteries. The present invention provides a preparation method of a PEO-based solid electrolyte, first by adding crown ether and high-concentration lithium salt to a PEO solid electrolyte to obtain a polymer solution; then a simple solution casting method and solidification are used to prepare a polymer solid electrolyte, which is simple to operate.
[0004] At the same time, the sulfide electrolyte has high ionic conductivity and good mechanical ductility. For example, patent CN118156593A also discloses a sulfide solid electrolyte membrane and its preparation method and application. The sulfide solid electrolyte membrane is composed of an ion-conductive polymer binder and a sulfide solid electrolyte, and the sulfide solid electrolyte is uniformly wrapped by the ion-conductive polymer binder; organic polymer A, lithium salt B and ionic liquid C are added to organic solvent D for mixing to obtain a uniform solution, and then the organic solvent is dried to remove the ion-conductive polymer binder to obtain an ion-conductive polymer binder; organic polymer A is a thermoplastic polymer electrolyte with a melting range of 40 to 140°C; organic polymer A has polar groups in its chemical structure; sulfide solid electrolyte powder and ion-conductive polymer binder are mixed and then a sulfide solid electrolyte membrane is prepared by a dry process.
[0005] Therefore, the advantages of both can be combined to prepare sulfide / polymer composite solid electrolytes, which can not only effectively reduce the thickness of the electrolyte layer and reduce the voltage polarization generated during the battery cycle, but also maintain high ionic conductivity characteristics, enhance the interface contact of the electrolyte / electrode material, and reduce the possibility of battery short circuit. Summary of the invention
[0006] By introducing lanthanum, the chemical stability of PEO is significantly improved, making it more suitable for use in complex electrochemical environments, and improving the conductivity of PEO-based electrolytes, because lanthanum ions can act as additional charge carriers to increase the conductivity of the system. It can also enhance the mechanical strength of the material, reduce the probability of breakage during use, and improve the overall safety of the battery. There may be an interaction between scandium bis(trifluoromethylsulfonyl)imide and Li6PS5Cl, which may affect the crystallinity and ion migration path of the material, thereby affecting the conductivity. Scandium ions in the composite electrolyte may help stabilize the interface between the electrode and the electrolyte, reduce the interfacial resistance, and improve the charge and discharge efficiency of the battery. The added scandium compound may have an expanding effect on the electrochemical window of the electrolyte, allowing the battery to operate in a wider voltage range. The addition of scandium may also enhance the thermal and mechanical stability of the electrolyte, allowing the battery to work properly in more extreme environments.
[0007] The purpose of the present invention can be achieved through the following technical solutions:
[0008] A method for preparing a lanthanum modified sulfide solid electrolyte, characterized in that it comprises the following steps:
[0009] (1) Preparation of Li6PS5Cl electrolyte: Li6PS5Cl solid electrolyte was prepared by solid phase sintering method. Lithium sulfide Li2S (Alfa, 99.9%), phosphorus sulfide P2S5 (Macklin, 99.9%), and lithium chloride LiCl (Aladdin, 99.9%) were used as initial raw materials. The raw materials were weighed according to appropriate amounts, poured into a ball mill jar, sealed, and placed in a ball mill for ball milling. Finally, the ball milled material was sealed in a quartz tube and sintered in a muffle furnace. The sintered electrolytic powder was finely ground for later use.
[0010] (2) Preparation of composite solid electrolyte: Lanthanum-modified polyethylene oxide and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI, Sigma-aldrich) and scandium bis(trifluoromethylsulfonyl)imide were mixed and then stirred evenly in anhydrous anisole (Sigma-aldrich, 99%). After that, Li6PS5C1 electrolyte powder was added to the lanthanum-modified polyethylene oxide-LiTFSI solution and stirred vigorously to ensure uniform mixing. Finally, the obtained slurry was dried to obtain a composite electrolyte. The composite solid electrolyte was named according to the content of lanthanum-modified PEO in the mixture.
[0011] The composite electrolyte was sandwiched between two lithium metal sheets to assemble a Li / LPSCI-PEO-LiTFSI / Li symmetric battery, which was then pressed into a custom insulating mold. NCM622 was used to assemble an NCM622 / LPSCI-PEO-LiTFSI / Li all-solid-state battery. The pressure was 150Mpa, and the loading amount of NCM622 was 6mg. All the above operations were carried out in a glove box filled with Ar atmosphere (oxygen partial pressure <0.1ppm, water partial pressure <0.1ppm).
[0012] As a preferred technical solution of the present invention, in step (1), the molar ratio of Li2S:P2S5:LiCl is 4-6:0.5-1.5:1-3.
[0013] As a preferred technical solution of the present invention, in step (1), the ball milling time is 0.5 to 1.5 hours, the calcination temperature is 500 to 600° C., and the calcination time is 20 to 60 minutes.
[0014] As a preferred technical solution of the present invention, in step (2), the molar ratio of the lanthanum-modified polyethylene oxide to lithium bis(trifluoromethanesulfonyl)imide and scandium bis(trifluoromethylsulfonyl)imide is 7-9: 1-1.3: 0.005-0.02.
[0015] As a preferred technical solution of the present invention, in step (2), the molar amount of anisole anhydrous is 10-20. As a preferred technical solution of the present invention, in step (2), the mass ratio of Li6PS5C1 electrolyte powder to lanthanum-modified polyethylene oxide is 0.93-0.97: 0.00003-0.0001;
[0016] As a preferred technical solution of the present invention, in step (2), the obtained slurry is dried at 150-200° C. for 1-5 h to obtain a composite electrolyte.
[0017] As a preferred technical solution of the present invention, the preparation method of the lanthanum-modified PEO is:
[0018] a1. Material preparation: Select PEO raw materials with an average molecular weight of 100,000 to 600,000, dry and crush them, and mix them with mercaptoethanol and lanthanum acrylate in a mass ratio of 0.00001:0.00001 to 0.00001:0.00003:0.2 to 0.3:0.05 to 0.1.
[0019] a2: After plasma treatment, post-treatment includes filtering, washing and drying to obtain lanthanum-modified PEO.
[0020] As a preferred technical solution of the present invention, the power of the low-temperature plasma is 120 to 200 W, and the processing time is 10 to 20 minutes.
[0021] As a preferred technical solution of the present invention, the gas flux setting is: using high-purity hydrogen and nitrogen, mixed in a volume ratio of 1-1.3:0.3-0.7, as a plasma treatment gas source.
[0022] As a preferred technical solution of the present invention, the controlled gas flow rate is 50-100 ml / min.
[0023] Beneficial effects of the present invention:
[0024] 1. Reaction mechanism of lanthanum-modified PEO
[0025] Introduction of thiol groups: Under low-temperature plasma conditions, PEO reacts with mercaptoethanol to introduce thiol groups. This modification increases the chemical activity of PEO and lays the foundation for further functionalization.
[0026] Introduction of amino groups: Subsequently, amino groups were successfully introduced into PEO in a low-temperature plasma environment of hydrogen and nitrogen. The introduction of amino groups not only improved the chemical stability of the material, but also enhanced its reactivity with other substances. Addition with lanthanum acrylate: After these two functionalization steps, the amino groups in PEO reacted with the carbon-carbon double bonds in lanthanum acrylate to form lanthanum-modified PEO. This step utilizes the nucleophilicity of the amino group and the electrophilicity of the carbon-carbon double bond to effectively connect the lanthanum element to the PEO chain.
[0027] 2. Technical Effect
[0028] Improved chemical stability: By introducing lanthanum, the chemical stability of PEO is significantly improved, making it more suitable for use in complex electrochemical environments.
[0029] Improvement of electrical conductivity: The addition of lanthanum may improve the electrical conductivity of PEO-based electrolytes because lanthanum ions can act as additional charge carriers, increasing the conductivity of the system.
[0030] Enhanced mechanical properties: Lanthanum modification can also enhance the mechanical strength of the material, reduce the probability of breakage during use, and improve the overall safety of the battery.
[0031] 3. Reaction mechanism of Li6PS5Cl electrolyte modified by scandium bis(trifluoromethylsulfonyl)imide
[0032] Preparation of composite electrolyte: Lanthanum-modified PEO is mixed with scandium bis(trifluoromethylsulfonyl)imide, and Li6PS5Cl is added to form a composite sulfide electrolyte. This composite material combines the advantages of each component, such as high conductivity and good chemical stability.
[0033] Interactions between substances: In the composite electrolyte, there may be interactions between scandium bis(trifluoromethylsulfonyl)imide and Li6PS5Cl, which may affect the crystallinity and ion migration path of the material, thereby affecting the conductivity.
[0034] 4. Technical Effect
[0035] Improved interface stability: Scandium ions in the composite electrolyte may help stabilize the interface between the electrode and the electrolyte, reduce the interface resistance, and improve the charge and discharge efficiency of the battery.
[0036] Improved electrochemical performance: The added scandium compounds may have the effect of expanding the electrochemical window of the electrolyte, allowing the battery to operate over a wider voltage range.
[0037] Enhanced structural stability: The addition of scandium may also enhance the thermal and mechanical stability of the electrolyte, allowing the battery to function properly in more extreme environments. DETAILED DESCRIPTION
[0038] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods and effects according to the present invention are described in detail below in conjunction with the embodiments.
[0039] Example 1
[0040] A method for preparing a lanthanum modified sulfide solid electrolyte comprises the following steps:
[0041] (1) Preparation of Li6PS5Cl electrolyte: Li6PS5Cl solid electrolyte was prepared by solid phase sintering method. 183.8g Li2S, 111.137g P2S5, 42.39g LiCl raw materials were weighed respectively, then poured into a ball milling jar and sealed, placed in a ball mill, the speed was set to 100rpm, and the ball milling time was 0.5h. Finally, the ball milled material was sealed in a quartz tube. Sintered at 500℃ in a muffle furnace for 20min, and the sintered electrolytic powder was finely ground for use.
[0042] (2) Preparation of composite solid electrolyte: 420g of lanthanum-modified polyethylene oxide, 287.08g of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI, Sigma-aldrich) and 4.425g of scandium bis(trifluoromethylsulfonyl)imide were mixed and then dissolved in 1080ml of anhydrous anisole (Sigma-aldrich, 99%) and stirred to form a uniform solution. Afterwards, 249.60g of Li6PS5C1 electrolyte powder was added to the lanthanum-modified PEO-LiTFSI solution containing 144g of lanthanum-modified PEO, and vigorously stirred at 70°C for 3h to ensure uniform mixing. Finally, the obtained slurry was dried at 150°C for 1h to obtain a composite electrolyte. The composite solid electrolyte is named according to the content of lanthanum-modified PEO in the mixture (3%).
[0043] The preparation method of the lanthanum modified PEO is:
[0044] a1. Material preparation: Select PEO raw materials with an average molecular weight of 100,000 to 500,000, dry and crush them, and mix them with mercaptoethanol and lanthanum acrylate in quantities of 60g, 15.6g and 3.6g, respectively.
[0045] a2: After plasma treatment, post-treatment includes filtering, washing and drying to obtain lanthanum-modified PEO, the low-temperature plasma power used is 120W, and the treatment time is 10min.
[0046] Gas flux setting: Use high-purity hydrogen and nitrogen mixed in a volume ratio of 1:0.3 as the plasma treatment gas source, and control the gas flow rate at 50 ml / min.
[0047] The composite electrolyte was sandwiched between two lithium metal sheets to assemble a Li / LPSCI-PEO-LiTFSI / Li symmetric battery, which was then pressed into a customized insulating mold. NCM622 was used to assemble the NCM622 / LPSCI-PEO-LiTFSI / Li all-solid-state battery. The pressure was 150Mpa, and the loading amount of NCM622 was 6mg. The above operations were all carried out in a glove box filled with Ar atmosphere (oxygen partial pressure <0.1ppm, water partial pressure <0.1ppm). At a current density of 0.1C, the initial discharge capacity of the NCM622 / LPSCI-LaPEO10%-LiTFSI / Li battery was as high as 125mAh g -1 After 100 cycles, the capacity retention rate is still 80.3%.
[0048] Example 2
[0049] A method for preparing a lanthanum modified sulfide solid electrolyte, which is different from Example 1 in that:
[0050] (1) Weigh 229.75 g Li2S, 222.273 g P2S5, and 84.78 g LiCl raw materials respectively, ball mill for 1 h, calcinate at 550 °C, and calcinate for 30 min.
[0051] (2) 480 g of lanthanum-modified PEO, 287.08 g of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI, Sigma-aldrich) and 8.85 g of scandium bis(trifluoromethylsulfonyl)imide were mixed, mixed, and then dissolved in 1620 ml of anhydrous anisole (Sigma-aldrich, 99%) and stirred to form a uniform solution. Afterwards, 260.35 g of Li6PS5C1 electrolyte powder was added to the lanthanum-modified PEO-LiTFSI solution containing 240 g of lanthanum-modified PEO, and vigorously stirred at 70 ° C for 3 h to ensure uniform mixing. Finally, the obtained slurry was dried at 170 ° C for 2 h to obtain a composite electrolyte. The composite solid electrolyte is named according to the content of lanthanum-modified PEO in the mixture (5%).
[0052] The preparation method of the lanthanum modified PEO is:
[0053] a1. Material preparation: Select PEO raw materials with an average molecular weight of 100,000 to 600,000, dry and crush them, and then weigh and mix them with mercaptoethanol and lanthanum acrylate in quantities of 72g, 19.5g and 5.4g respectively.
[0054] a2: After plasma treatment, post-treatment includes filtering, washing and drying to obtain lanthanum-modified PEO, the low-temperature plasma power used is 160W, and the treatment time is 15min.
[0055] Gas flux setting: Use high-purity hydrogen and nitrogen mixed in a volume ratio of 1.2:0.5 as the plasma treatment gas source, and control the gas flow rate at 75 ml / min.
[0056] At a current density of 0.1C, the initial discharge capacity of the NCM622 / LPSCI-LaPEO3%-LiTFSI / Li battery is as high as 131 mAh g -1 , after 100 cycles, the capacity retention rate is still 85%.
[0057] Example 3
[0058] A method for preparing a lanthanum modified sulfide solid electrolyte, which is different from Example 1 in that:
[0059] Weigh 275.7g Li2S, 333.41g P2S5, and 127.17g LiCl raw materials respectively.
[0060] (1) Weigh 183.8 g Li2S, 111.137 g P2S5, and 42.39 g LiCl raw materials respectively, ball mill for 1.5 h, calcinate at 600 °C, and calcinate for 60 min.
[0061] (2) 540 g PEO (molecular weight 600,000, Sigma-aldrich) and 287.08 g lithium bis(trifluoromethanesulfonyl)imide (LiTFSI, Sigma-aldrich) were mixed and then dissolved in 2160 ml anhydrous anisole (Sigma-aldrich, 99%) and stirred to form a uniform solution. Afterwards, 254.97 g Li6PS5C1 electrolyte powder was added to the lanthanum-modified PEO-LiTFSI solution containing 480 g lanthanum-modified PEO, and vigorously stirred at 70 ° C for 3 h to ensure uniform mixing. Finally, the obtained slurry was dried at 200 ° C for 5 h to obtain a composite electrolyte. The composite solid electrolyte is named according to the content of lanthanum-modified PEO in the mixture (10%).
[0062] The preparation method of the lanthanum modified PEO is:
[0063] a1. Material preparation: Select PEO raw materials with an average molecular weight of 100,000 to 600,000, dry and crush them, and then weigh and mix them with mercaptoethanol and lanthanum acrylate in quantities of 78g, 23.4g and 7.2g respectively.
[0064] a2: After plasma treatment, post-treatment includes filtering, washing and drying to obtain lanthanum-modified PEO, wherein the low-temperature plasma power is 200W and the treatment time is 20min.
[0065] Gas flux setting: Use high-purity hydrogen and nitrogen mixed in a volume ratio of 1.3:0.7 as the plasma treatment gas source, and control the gas flow rate at 100 ml / min.
[0066] At a current density of 0.1C, the initial discharge capacity of NCM622 / LPSCI-LaPEO5%-LiTFSI / Li battery is as high as 135.5 mAh g -1 After 100 cycles, the capacity retention rate is still 89.2%.
[0067] Comparative Example 1
[0068] (2) Weigh 229.75 g Li2S, 222.273 g P2S5, and 84.78 g LiCl raw materials respectively, ball mill for 1 h, calcinate at 550 °C, and calcinate for 30 min.
[0069] (2) 480 g of PEO (molecular weight 600,000, Sigma-aldrich) and 287.08 g of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI, Sigma-aldrich) were mixed and then dissolved in anhydrous anisole (Sigma-aldrich, 99%) and stirred to form a uniform solution. Afterwards, 260.35 g of Li6PS5C1 electrolyte powder was added to the PEO-LiTFSI solution containing 144 g of PEO and vigorously stirred at 70 ° C for 3 h to ensure uniform mixing. Finally, the obtained slurry was dried at 150 ° C for 1 h to obtain a composite electrolyte. The composite solid electrolyte is named according to the content of PEO in the mixture (5%).
[0070] The composite electrolyte was sandwiched between two lithium metal sheets to assemble a Li / LPSCI-PEO-LiTFSI / Li symmetrical battery, and then pressed into a customized insulating mold. NCM622 was used to assemble the NCM622 / LPSCI-PEO-LiTFSI / Li all-solid-state battery. The pressure was 150Mpa, and the loading amount of NCM622 was 6mg. The above operations were all carried out in a glove box filled with Ar atmosphere (oxygen partial pressure <0.1ppm, water partial pressure <0.1ppm). At a current density of 0.1C, the initial discharge capacity of the NCM622 / LPSCI-PEO3%-LiTFSI / Li battery was as high as 110.5mAhg -1 , after 100 cycles, the capacity retention rate is still 70.2%.
Claims
1. A method for preparing a lanthanum modified sulfide solid electrolyte, characterized in that: The following steps are involved: (1) Preparation of Li6PS5Cl electrolyte: Li6PS5Cl solid electrolyte was prepared by solid phase sintering method. Lithium sulfide Li2S, phosphorus sulfide P2S5, and lithium chloride LiCl were used as initial raw materials. The raw materials were weighed according to appropriate amounts, poured into a ball mill jar and sealed, and placed in a ball mill for ball milling. Finally, the ball milled material was sealed in a quartz tube and sintered in a muffle furnace. The sintered electrolytic powder was finely ground for later use. (2) Preparation of composite solid electrolyte: Lanthanum-modified polyethylene oxide and lithium bis(trifluoromethanesulfonyl)imide and scandium bis(trifluoromethylsulfonyl)imide are mixed and then stirred evenly in anhydrous anisole. Thereafter, Li6PS5C1 electrolyte powder is added to the lanthanum-modified PEO-LiTFSI solution and stirred vigorously to ensure uniform mixing. Finally, the obtained slurry is dried to obtain a composite electrolyte. The composite solid electrolyte is named according to the content of lanthanum-modified PEO in the mixture. The composite electrolyte was sandwiched between two lithium metal sheets to assemble a Li / LPSCI-PEO-LiTFSI / Li symmetric battery, which was then pressed into a custom insulating mold. NCM622 was used to assemble an NCM622 / LPSCI-PEO-LiTFSI / Li all-solid-state battery. The pressure was 150Mpa, and the loading amount of NCM622 was 6mg. All the above operations were carried out in a glove box filled with Ar atmosphere (oxygen partial pressure <0.1ppm, water partial pressure <0.1ppm).
2. The method for preparing a lanthanum-modified sulfide solid electrolyte according to claim 1, characterized in that: In step (1), the molar ratio of Li2S:P2S5:LiCl is 4-6:0.5-1.5:1-3.
3. The method for preparing a lanthanum-modified sulfide solid electrolyte according to claim 1, characterized in that: In step (1), the ball milling time is 0.5 to 1.5 hours, the calcination temperature is 500 to 600° C., and the calcination time is 20 to 60 minutes.
4. The method for preparing a lanthanum-modified sulfide solid electrolyte according to claim 1, characterized in that: In step (2), the molar ratio of the lanthanum-modified polyethylene oxide to lithium bis(trifluoromethanesulfonyl)imide and scandium bis(trifluoromethylsulfonyl)imide is 7-9: 1-1.3: 0.005-0.
02.
5. The method for preparing a lanthanum modified sulfide solid electrolyte according to claim 1, characterized in that: In step (2), the molar amount of anisole anhydrous is 10-20.
6. The method for preparing a lanthanum-modified sulfide solid electrolyte according to claim 1, characterized in that: In step (2), the mass ratio of the Li6PS5C1 electrolyte powder to the lanthanum-modified polyethylene oxide is 0.93-0.97:0.00003-0.0001.
7. The method for preparing a lanthanum modified sulfide solid electrolyte according to claim 1, characterized in that: In step (2), the obtained slurry is dried at 150-200° C. for 1-5 h to obtain a composite electrolyte.
8. The method for preparing a lanthanum modified sulfide solid electrolyte according to claim 1, characterized in that: The preparation method of the lanthanum modified PEO is: a1. Material preparation: Select PEO raw materials with an average molecular weight of 100,000 to 600,000, dry and crush them, and mix them with mercaptoethanol and lanthanum acrylate in a mass ratio of 0.00001:0.00001 to 0.00001:0.00003:0.2 to 0.3:0.05 to 0.
1. a2. After plasma treatment, post-treatment includes filtering, washing and drying to obtain lanthanum-modified PEO.
9. The method for preparing a lanthanum-modified sulfide solid electrolyte according to claim 7, characterized in that: The low-temperature plasma power is 120-200W, and the treatment time is 10-20min.
10. The method for preparing a lanthanum modified sulfide solid electrolyte according to claim 7, characterized in that: Gas flux setting: Use high-purity hydrogen and nitrogen, mixed in a volume ratio of 1-1.3:0.3-0.7, as the plasma treatment gas source.
11. The method for preparing a lanthanum modified sulfide solid electrolyte according to claim 7, characterized in that: Control the gas flow rate at 50-100 ml / min.
Citation Information
Patent Citations
PEO-based solid electrolyte as well as preparation method and application thereof
CN117096430A